Capstone Project Data Analyst Pada Studi Independen Bersertifikat di Revou Tech Academy Batch 5: Analisis Data Untuk Meningkatkan Penjualan Produk Pada E-Commerce Fashion di Australia - Humaira, Ummi Rawdlah; Istiqamah, St. Hadjar Nurul (CV. Ulil Albab Corp, 2024)
Studi Independen Bersertifikat Program Batch 5 at RevoU Tech Academy presents learning programs that focus on software engineering and data analysis. These two positions are considered important in today's digital world. Apart from that, in order to improve the quality of human resources in the face of the complexity of the Industrial Revolution 4.0. This program will equip students to be ready to face the world of work with adequate knowledge and experience. The capstone project is one of the learning methods applied to evaluate students' knowledge and hone their practical skills regarding software engineering and data analyst material. The Capstone Project in the Data Analyst module at this partner uses datasets from fashion e-commerce in Australia. In e-commerce, it is known that there has been a decline in sales for the last 3 months. The methods of descriptive analysis, exploratory data analysis, and root cause analysis (RCA) are used in data analysis. The findings of the analysis show that while product sales are not directly impacted by seasonal variables, they can be made as profitable as possible by using marketing strategies that adapt to seasonal trends, enhancing delivery procedures, and putting more of an emphasis on target consumers. As a component of the RevoU Tech Academy's learning methodology, the Capstone Project demonstrates the critical role in developing human resources prepared to handle shifting industrial dynamics. In addition, students will receive pertinent knowledge and abilities to help them deal with the difficulties of the contemporary technological world.